Desigualdade de Hölder generalizada com normas mistas e aplicacões - Araújo, Daniel Tomaz de (2016)
In this work, we present a version little know of the famous Hölder's Inequality, considering the context of Lp and lp spaces for mixed norms. We show how a suitable use this inequality has influencied positively others classical inequalities, to highlight, the multilinear inequalities of Bohnenblust-Hille and Hardy-Littlewood.